Performance and Haematological Profile of Broiler Chickens Fed Diet Containing Atung (Parinarium glaberrimumHassk.) Seed Powder - Sylvia C. H. Hehanussa; Zuprizal Zuprizal; Chusnul Hanim; Nanung Danar Dono (Buletin Peternakan, 2022)
This study investigated the effect of feeding atung (Parinarium glaberrimum Hassk.) seed meal on growth performance and haematology profile in broiler chickens. A total of 140 one-day-old male New Lohmann broiler chicks were randomly assigned to five treatment groups with four replicates and seven birds in each replicate pen. The dietary treatments consisted of feeding the same corn-soybean meal as the basal diet with atung seed powder inclusions at levels of 0, 0.5, 1.0, 2.0, and 4.0%, respectively. The data were statistically analyzed using One-way with five treatments and four replications and continued with Duncan's New Multiple Range Test for data with a significant difference. Results showed that feed intake increased (p<0.05) in broiler chickens fed diets with 0.5 and 1% atung seed powder. At the same time, the inclusion of atung seed powder had no effect on final body weight, weight gain, and FCR. Inclusion of 1 and 2% atung seed powder significantly increased leucocyte counts, as well as the PCV value trend increased with the inclusion of atung seed powder. It can be concluded that atung seed powder additives can be supplemented in broiler chickens feed at doses 1% by improving feed intake and some haematological profiles.